Severity and Control Levels of Bronchial Asthma in the Pediatric Population of Yamanigüey. Moa - Alexander Torres Molina; Yamila Loforte Columbié (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Background: Bronchial asthma is the most common chronic disease in childhood. It is clinically and epidemiologically stratified according to its degree of severity and we argue for its classification according to control levels. Objective: To characterize asthmatic patients from two to seventeen years old by using the degree of severity and the control levels as parameters. Methods: A descriptive study that included 88 children and adolescents suffering from asthma in the village Yamanigüey, Moa, was conducted from January to December 2010. In these patients, there were identified different clinical and demographic variables. Results: 28.02% of this population suffers from bronchial asthma. 53.41% of patients are females and 39.78% are from 14 to17 years old. Only three cases (3.41%) present severe and persistent asthma and they coincide with uncontrolled cases. 100% of patients with and severe persistent asthma and moderate persistent asthma were not controlled or only partially controlled. Conclusions: Patients with intermittent and mild asthma predominated. A link was found between disease's severity and control levels.